The Effect of Using Scrabble Games towards Students’ Achievement in Vocabulary - Dwi Purnama; Rini Fadhillah Putri (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2022)
The objective of this research was to find out the significant effect of using scrabble games towards students’ achievement in vocabulary at the eighth grade of SMP Negeri 2 Deli Tua. The type of research was quantitative research, and it was conducted by using experimental design with two classes, in experimental class and control class consisted of 26 students. In technique of collecting data, the researcher conducted pre-test, treatment and post-test by vocabulary test. The data were analyzed by using mean, standard deviation and t-test formula. The result of the data showed that t-observe (12.19) value was higher than the t-table in which t-observe > t-table (12.19 >1.68). The finding showed that the hypothesis was accepted. It can be concluded that there was significant difference score in vocabulary achievement for the students who were taught by using scrabble games and who were not taught by using scrabble games. Based on the explanation above, the researcher concluded that scrabble games is effective for teaching vocabulary of the eighth grade students at SMP Negeri 2 Deli Tua Academic Year 2021/2022